PTU-167 Enhanced recovery for laparoscopic colorectal resection: is there a role for transcutaneous electrical nerve stimulation?. (22nd June 2015) - El-Sayed, C; Singh-Ranger, D; Aslam, I; Khan, M; Francombe, J
Abstract : Introduction: Transcutaneous electrical nerve stimulation (TENS) is a recognised modality for pain control. Evidence for its use in enhanced recovery programmes is limited. This pilot study aimed to investigate the role of TENS in pain control, ileus and duration of stay in patients undergoing elective colorectal surgery within an enhanced recovery programme. Method: Patients undergoing elective laparoscopic colorectal resection were given TENS twice daily for thirty minutes. This was in addition to standard analgesic and fluid regimens. Patients completed a visual analogue score (VAS) pain questionnaire daily during the post-operative period. Pain was assessed at three points: 1. At rest, 2. Transferring out of bed, 3. Mobilisation. The difference in pain scores, analgesic requirements, time to first flatus and hospital stay were recorded. Results: Seven patients used the TENS machine, four patients were controls. The median age was 77 years (61–79). The higher the VAS score, the greater the pain. The average pain score over four days in the TENS group vs. control group at rest, transfer and mobilisation was 30.9 vs. 47; 49.6 vs. 57.8 and 39.7 vs. 55.3 respectively. The differences between TENS and the control group were significant at rest (p = 0.046) and mobilisation (p = 0.040). The average cumulative paracetamol and ibuprofen dose in TENS patients was reduced compared to the control group (1.5 g vs. 2.6 g) and (2 g vs. 2.75 g) respectively. TENS reduced hospital stay (5.6 vs. 6.6 days) and reduced the time to pass flatus (1.75 vs. 2 day). This trend was not significant. Conclusion: TENS is recommended as an effective addition to an enhanced recovery programme in patients undergoing laparoscopic colorectal surgery. TENS significantly reduced post operative pain at rest and transfer. There was also a trend in reduction of ileus, analgesic use and length of stay. Disclosure of interest: None Declared.